Characterizing plastic pollution on beaches of Cozumel Island, Mexico: abundance, distribution, and influencing factors - Mansilla-García, Ana Victoria; Cuarón, Alfredo; Vázquez, Luis-Bernardo (Revista Ciencias Marinas y Costeras, 2024)
Plastic pollution in marine environments represents a significant threat to ecosystems worldwide. This study focuses on Cozumel Island, located in the Caribbean Sea, where plastic debris, primarily from inadequate management, adversely affects its beaches. Nine beaches were selected to conduct debris sampling and determine the abundance, density, and type of objects found at the sites. Three sampling repetitions were conducted on the surface of each beach, while three samplings were conducted on eight beaches to analyze buried debris. One of the beaches was discarded for buried debris sampling because of its rocky composition. Data was collected between March 22 and June 15, 2019. A total of 25,102 surface debris items were found, 94% of which were plastic. Similarly, 4,365 buried items were recorded, with the vast majority (97.8%) being plastic debris. Surface and buried debris densities vary, influenced by factors such as beach location, substrate composition, and human visitation. Beaches with lower human presence exhibit the highest debris densities, particularly in windward areas. Statistical models indicate that low-to-medium visitor influx and beach location significantly impact debris characteristics. Insights from this research contribute to understanding the dynamics of marine debris on Cozumel beaches, which plays a crucial role in informed policymaking and conservation efforts.